The roles of Tuha Peut Gampong in healthcare services for pregnant women - Farisni, Teungku Nih; Fitriani, Fitriani; Indriasari, Rahayu; Yarmaliza, Yarmaliza; Putra, Onetusfifsi (Jurnal Kesehatan Masyarakat, 2023)
This research was aimed to identify the roles of Tuha Peut in healthcare service for pregnant women. This study was also examined the obstacles of Tuha Peut in implementing the roles and identified the efforts taken to strengthen the roles. This research employed quantitative and qualitative approaches. The quantitative approach using a questionnaire to collect data was used to provide indicators for maternal healthcare and the knowledge of Tuha Peut towards maternal health care. Meanwhile, the qualitative approach using open-ended interview guide and focus group discussion (FGD) was employed to explore the constraints and efforts in improving maternal healthcare. The research location was in Nagan Raya, Aceh Province. A total of 48 respondents was recruited in this study. The result shows there is a relevance between the health care achievement and TuhaPeut knowledge as the legislative assembly in decision making regarding the village fund (p 0.001). Concerning the decision-making, most Tuha Peut were not involved in decision-making related to the health sector. Some of them were only passively involved, and some could not provide considerations for maternal healthcare. Unfortunately, efforts to maximize their roles in improving maternal healthcare had not been carried out. It is recommended that TuhaPeut can be more involved in every planning process of maternal healthcare service, such as arranging Qanun as the jurisdictional basis. Tuha Peut’s roles can be maximized to increase the health care for pregnant mothers.